Anterior Segment Optical Coherence Tomography Imaging of Filtering Blebs after Deep Sclerectomy with Esnoper-Clip Implant: One-year Follow-up - Vieira, Luisa (J Curr Glaucoma Pract, 2014)
Purpose: To describe the technique of deep sclerectomy with the new Esnoper-Clip® implant, the clinical outcome and the anatomic characteristics of filtering blebs, using anterior segment optical coherence tomography (AS-OCT). Methods: A prospective case-series study was conducted in five eyes (5 patients) with open angle glaucoma. The fornix-based deep sclerectomy with Esnoper-Clip® implant was done by the same surgeon. In one case, mitomycin C was used during surgery. All participants underwent a complete ophthalmic examination and AS-OCT (Visante®) preoperatively, then at each follow-up visit, at 1 day, 1 week, 1 month, 6 months and 1 year postoperatively. Scans were obtained through sagittal and transversal plans to the implant. Results: Intraocular pressure (IOP) was significantly reduced (p < 0.05) from a mean preoperative value of 23.4 ± 8.6 mm Hg (n = 3.8 glaucoma medications) to a postoperative value of 6.0 ± 2.5 (n = 0), 10.6 ± 5.4 (n = 0), 13 ± 1.6 (n = 0.4), 12.4 ± 2.1 (n = 0.2) and 14.4 ± 1.5 (n = 0.2) at 1 day, 1 week, 1 month, 6 months and 1 year respectively. AS-OCT allowed the visualization of the two plates of the implant (scleral and suprasciliary), the trabeculodescemetic membrane and the hyporeflective spaces in the bleb wall thickness and in suprascleral and suprachoroidal localizations. An immediate postoperative hypotony and an anteriorization of the implant associated to trabeculodescemetic membrane rupture, were detected, although without significant clinical repercussions. Conclusion: Our first five deep sclerectomy with Esnoper-Clip implantation analysis suggest an effective and well-tolerated method to reduce IOP. AS-OCT is a noninvasive imaging technique that allows the anatomic analysis of the drainage mechanisms after glaucoma surgery. How to cite this article: Vieira L, Noronha M, Lemos V, Reina M, Gomes T. Anterior Segment Optical Coherence Tomography Imaging of Filtering Blebs after Deep Sclerectomy with Esnoper-Clip Implant: One-year Follow-up. J Curr Glaucoma Pract 2014;8(3):91-95.